TOUR ATTENDANTS IN GROUP TRAVELS: DRIVING THE CREATION OF TOURIST EXIRIENCES - Stefanović, Jelena; Štilić, Anđelka; Pavković, Vladimir; Beganović, Admir (ACADEMIC REVIEW, 2023)
This paper presents research on the pivotal role of tour attendants in group travels and their impact on the quality of tourist experiences. The primary objective is to explore how tourists’ expectations and preferences regarding tour attendants influence their experiences during such journeys. Conducted through an online questionnaire, the study surveyed 715 respondents across various age groups to analyze travelers’ perspectives on the role of tour attendants, their expectations during tours, and the factors shaping travel experiences. The findings underscore the significance of tour attendants in curating high-quality experiences, highlighting the crucial need for relevant information dissemination and the proactive involvement of tour attendants in enhancing these experiences.